Investigation of the pro-oxidative and pro-inflammatory interactions of cobalt, palladium, platinum and vanadium with human neutrophils in vitro - Anderson, Ronald (University of Pretoria, 2013)
Thesis (PhD (Medical Immunology))--University of Pretoria, 2008.